ONTOLOGY OF NATIONAL IDENTITY IN THE SPACE OF MODERN CULTURES AND CIVILIZATIONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article is devoted to the study of the ontology of national identity in the space of modern cultures and civilizations. Ontology is a philosophical discipline that studies the essence of being and the existence of each specific thing or event. National identity, in turn, is a complex concept covering many aspects, including language, culture, history, values, symbols and traditions. The author substantiates the relevance of studying this problem in the modern world, where globalization has led to the blurring of boundaries and differentiation of national identity. The author also emphasizes the importance of developing ontological concepts that will allow us to more deeply understand and analyze the processes of formation of national identity in modern society.
Keywords: identity, national identity, existence of a nation, ontology of identity, culture, civilization, modernity, dialogue of cultures.